Quality Evaluation and Flavonoid Content of Honey from Riau Forest, Indonesia - Yuniritha, Eva; Habibi, Nur Ahmad; Hasneli, Hasneli; Doni, Alsri Windra (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2024)
Honey is a naturally sweet liquid produced by bees from flower nectar, which varies in quality and flavonoid content due to the food source, environment and the bees that produce it. This study aims to evaluate the quality and flavonoid content of honey from the Riau Forest of Indonesia. Quality testing was conducted in accordance with SNI 8664:2018 with sensory, physical, chemical and microbiological parameters. Flavonoid testing was carried out qualitatively using HPLC. The test results showed that the sensory profile of honey was in accordance with the standard, sweet taste, distinctive aroma, brown colour and thick shape. Chemical parameters obtained values of moisture content of 21.92%, diastase enzyme 3.13 DN and HMF 4.14 mg/kg have met the requirements. However, the reducing sugar of 54.1% is still below the requirement. Heavy metal parameters (Pb, Cd, As and Hg) were not detected and microbiological ALT 3.0 x 10 and yeast mould <10 colonies/gr that have met. Furthermore, the results of flavonoid qualitative tests detected several types including Luteolin, Mangiferin, Smiglanin, maltol, isoflavones, quercetin, Cnidimol C, Norcimifungin, Apigenin, Methyl ophiopogonanone B, Pectolinarigenin, Kusenol C, 3,5,6-trihydroxy-4',7-dimetoxyflavone and Lupinifoline. The conclusion of this study shows that honey from Riau forests fulfils most of the quality requirements and has a diverse flavonoid content.